United Arab Emirates : 2004 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the United Arab Emirates. (IMF Staff Country Reports; Country Report, 2004)
This 2004 Article IV Consultation highlights that the macroeconomic performance of United Arab Emirates is estimated to have been strong in 2003, reflecting favorable developments in the oil market, higher oil production, and prices. Non-hydrocarbon real GDP growth is estimated to have remained robust at about 5 percent, one of the highest in the Gulf Cooperation Council area. Several projects were launched in 2003 in the areas of construction, upstream gas, and downstream oil services. Progress in introducing structural reforms has varied among the Emirates.